Real-time multiple cross displacement amplification assay for rapid and sensitive detection of Haemophilus influenzae - Sun, Chunrong; Jia, Nan; Huang, Xiaolan; Xiao, Fei; Zhou, Juan; Zhang, Yu; Fu, Jin; Xu, Zheng; Qu, Dong; Cui, Xiaodai; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Haemophilus influenzae is an opportunistic pathogen usually causing bacteremia, meningitis and pneumonia in children. Here, we developed a method based on multiple cross displacement amplification (MCDA) strategy and real-time fluorescence detection technique for rapid detection of H. influenzae. A set of ten primers were designed for the MCDA reaction. The MCDA reactions were real-time monitored using fluorescence quantitative PCR instrument through a fluorescent labeled primer. The recommended condition for the MCDA reaction is 40 minutes at 63 °C. The H. influenzae real-time MCDA (RT-MCDA) assay can specifically detect H. influenzae without any cross reaction with other bacteria as our results confirmed. The sensitivity of the assay is as low as 37.6 fg per reaction. In particular, the assay was applied to 40 DNA isolates from sputum samples for clinical feasibility evaluation. And the results were compared with that of loop mediated isothermal amplification (LAMP) test and visually confirmed by lateral flow biosensor (LFB). The positive rate of RT-MCDA assay was 62.5% equal with that of MCDA-LFB assay, and that of the LAMP test was 57.5%. The H. influenzae RT-MCDA assay takes only 40 min, less than that of traditional PCR test. In conclusion, the H. influenzae RT-MCDA assay offers a new option for reliable, simple and rapid detection of H. influenzae.